An examination of relationships between vitamin B12 status and functional measures of peripheral neuropathy in young adult vegetarians - Arnold, Taylor; Johnston, Carol S. (Frontiers in Nutrition, 2023)
Prevalence rates for vitamin B12 deficiency in U.S. adult vegetarians may exceed 30%, which is concerning given the role for this vitamin in numerous nervous system functions, including the synthesis of myelin sheaths. Defective myelin synthesis and repair are directly linked to peripheral neuropathy; yet, few investigations have examined how physical indicators of peripheral neuropathy (e.g., hand dexterity, vibration sensitivity and balance) are impacted in individuals adhering to vegetarian diets. This feasibility research explored the relationships between peripheral neuropathy and vitamin B12 status using a cross-sectional study design. In addition, a small pilot trial was conducted for limited-efficacy testing of vitamin B12 supplementation for reducing peripheral neuropathy. Healthy, able-bodied adults (n=38; 19-40 years of age) reported exclusive adherence to a vegetarian or vegan diet for 3 years. Peripheral neuropathy was measured using a force plate for assessing balance, and a vibration sensitivity tester and pegboard tests to assess hand dexterity. Serum vitamin B12 and folate were measured using standard radioimmunoassay techniques. Twenty-six percent of the sample displayed deficient or marginal vitamin B12 status (serum vitamin B12 <221 pmol/L). Participants with adequate vitamin B12 status scored 10% higher on the Purdue pegboard assembly test and 20% higher on the left hand adjusted functional dexterity test in comparison to participants with marginal-to-deficient vitamin B12 status (p<0.05). These data provide preliminary evidence that peripheral neuropathy can be detected in individuals with marginal-to-deficient vitamin B12 status.